2022
DOI: 10.18677/encibio_2022d2
|View full text |Cite
|
Sign up to set email alerts
|

A Inseminação Artificial Em Bovinos De Corte No Brasil

Abstract: RESUMOA Inseminação Artificial (IA) é uma biotecnologia reprodutiva usada como ferramenta para o melhoramento genético dos bovinos, destacando-se a seleção e a replicação de touros de alto valor genético, possibilitando a obtenção de bezerros mais qualificados, com incremento de produtividade e de receita. Objetivou-se conhecer a história, compreender a evolução e entender a influência da biotecnologia Inseminação Artificial em bovinos de corte no Brasil. Houve um crescimento populacional rápido, gerando deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The pregnancy rates obtained in this study are favorable at TAI and our results corroborate those observed by Nonato et al (2019) who found pregnancy rates of 45% to 59% in pubertal and pre-pubertal Nelore heifers. Pregnancy rates between 40% and 60% gestation rate are considered satisfactory when compared to the national average in TAI rograms (Sales et al, 2014;Andrade et al, 2018). Heifers are represented as the group of animals of primary importance in any production system, because they will be the possible replacements cows, so the earlier an animal contribute te the breeding herd, greater the economic impact on the productivity of the livestock sector, because heifers that conceive early will produce more calves and have their life cycle intensified.…”
Section: Resultsmentioning
confidence: 99%
“…The pregnancy rates obtained in this study are favorable at TAI and our results corroborate those observed by Nonato et al (2019) who found pregnancy rates of 45% to 59% in pubertal and pre-pubertal Nelore heifers. Pregnancy rates between 40% and 60% gestation rate are considered satisfactory when compared to the national average in TAI rograms (Sales et al, 2014;Andrade et al, 2018). Heifers are represented as the group of animals of primary importance in any production system, because they will be the possible replacements cows, so the earlier an animal contribute te the breeding herd, greater the economic impact on the productivity of the livestock sector, because heifers that conceive early will produce more calves and have their life cycle intensified.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, researchers have aimed to increase the PR of FTAI in cattle (Sales et al., 2014) by altering protocols. These protocols have been modified through the introduction of new drugs, such as bST, and through management and nutritional procedures (Silva et al., 2019; Sousa et al., 2017).…”
Section: Discussionmentioning
confidence: 99%